2009
DOI: 10.1021/ja901006x
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of the Cobalt Particle Size Effects in Fischer−Tropsch Catalysis

Abstract: The effects of metal particle size in catalysis are of prime scientific and industrial importance and call for a better understanding. In this paper the origin of the cobalt particle size effects in Fischer-Tropsch (FT) catalysis was studied. Steady-State Isotopic Transient Kinetic Analysis (SSITKA) was applied to provide surface residence times and coverages of reaction intermediates as a function of Co particle size (2.6-16 nm). For carbon nanofiber supported cobalt catalysts at 210 degrees C and H(2)/CO = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
610
4
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(698 citation statements)
references
References 66 publications
51
610
4
8
Order By: Relevance
“…[28][29][30] In this range, the turnover frequency of the Co catalyst does not change with particle size. 31 Both the as-synthesized Co nanorods and the nanoparticles have the Co 3 O 4 spinel structure (PDF 41-1467), as determined by powder X-ray diffraction, see insets in The crystal facets exposed on the nanorod and nanoparticle surfaces were characterized with high resolution TEM, see 20 In contrast, the Co nanoparticles exhibit {001} and {111} facets at their surfaces (Fig. 1b), which is consistent with literature.…”
supporting
confidence: 84%
“…[28][29][30] In this range, the turnover frequency of the Co catalyst does not change with particle size. 31 Both the as-synthesized Co nanorods and the nanoparticles have the Co 3 O 4 spinel structure (PDF 41-1467), as determined by powder X-ray diffraction, see insets in The crystal facets exposed on the nanorod and nanoparticle surfaces were characterized with high resolution TEM, see 20 In contrast, the Co nanoparticles exhibit {001} and {111} facets at their surfaces (Fig. 1b), which is consistent with literature.…”
supporting
confidence: 84%
“…For FTS, the use of SSITKA has resulted in an improved understanding on the effect of catalyst properties (promoters [72][73][74][75][76][77][78][79][80][81][82][83], support [84][85][86][87][88][89][90], particle size etc. [91][92][93][94]) and the reaction conditions [95][96][97][98][99][100][101] on the performance. Concerning the mechanism, SSITKA gives the coverage of CO and surface carbon intermediates and the site coverage of H can be estimated.…”
Section: Approaches Of Kinetic Analysis For Ftsmentioning
confidence: 99%
“…Recently, the increase in demand for transportation fuels and the large reserves of natural gas have made FTS an attractive industrial process. In the FTS process, cobaltbased catalysts, owing to low water-gas shift activity and remarkable stability, is considered to be the favorable catalyst for the synthesis of long-chain hydrocarbons from synthesis gas with a H 2 /CO ratio about 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially problematic with spectroscopic tools like EXAFS, which take a volume not a surface average. A number of routes have now been developed that allow for better control of particle size:  carbon nanofibres (CNFs) with oxide defects to anchor / control particle growth during incipient wetness preparation; 39 49 As shown in Table 2, the first four of these methods have yielded the clear result that small particles (below around 7 nm or less) are intrinsically less active (and where looked at also less selective towards higher molecular weight products). For CNF anchored nanoparticles at both 1 and 35 bar a significant decrease in site time yield was observed for samples with nanoparticles smaller than 6 nm.…”
Section: Molecular Level Understanding Of Ft Catalysis On Cobaltmentioning
confidence: 99%
“…For CNF anchored nanoparticles at both 1 and 35 bar a significant decrease in site time yield was observed for samples with nanoparticles smaller than 6 nm. 39,40 CNF supports were selected to eliminate the possibility of oxide supports oxidising the cobalt. Using SSITKA the authors showed small nanoparticles had a greater fraction of sites occupied by irreversibly adsorbed CO.…”
Section: Molecular Level Understanding Of Ft Catalysis On Cobaltmentioning
confidence: 99%